Cognitive Training in a Large Group of Patients Affected by Early-Stage Alzheimer's Disease can have Long-Lasting Effects: A Case-Control Study. Issue 2 (11th March 2016) - Cavallo, Marco; Zanalda, Enrico; Johnston, Harriet; Bonansea, Alessandro; Angilletta, Chiara
Abstract : Introduction: Cognitive training in Alzheimer's disease (AD) has recently started to demonstrate its efficacy. We used our 'puzzle-like' task (GEO) as training for a large group of early-stage AD patients, to detect its effects over time. Method: AD patients ( N = 40) and healthy controls ( N = 40) were involved. Participants were administered the Geographical Exercises for cognitive Optimization (GEO) task. Participants underwent individual sessions with GEO three times a week for 2 months, and then their performance was recorded again. Lastly, at the 12-month follow-up the GEO task was administered for the last time. Results: Patients' scores were significantly worse than controls' scores only on a few neuropsychological tests. We ran a repeated measures GLM by considering groups' performance on the GEO task at the assessment points. Results showed a significant main effect of group, and a significant effect of the interaction between group and time : patients' performances both at the end of the training and at the follow-up were virtually identical to controls' performances. Conclusions: Patients effectively acquired new procedural abilities, and their achievements were stable at follow-up. This study suggests the GEO is a useful strategy for cognitive training in AD, and should prompt further investigations about the degree of generalisability of patients' acquired skills.